Engagement through online discussion: perceptions of laying hen welfare in furnished cages. (7th January 2019) - Rohlf, V. I.; Howell, T. J.; Coleman, G.; Rault, J.-L.
Abstract : Furnished cage housing for laying hens has been introduced in some countries as a 'welfare-friendly' alternative to conventional cage systems. Whether this housing system would be acceptable to the public remains unknown. This pilot study aimed to engage the public through online discussions in order to investigate their knowledge, support and perception of laying hen welfare housed in furnished cages. During these discussions, a science-based information statement about furnished cages was introduced. Through a mixed method approach, surveys to assess beliefs and knowledge were administered to participants before and after the online discussion. We qualitatively analysed the online discussion transcripts to determine recurrent themes, and quantitatively measured levels of knowledge and support for furnished cages using pre- and post-forum surveys. Support for the introduction increased from 55% pre-forum to 65% post-forum. Additionally, the participants' perceived welfare of laying hens in furnished cages and objective knowledge of furnished cages significantly increased after online discussion. These results suggest that engagement with the public combined with the delivery of science-based information may be important factors when considering whether to introduce new farming practices. Trust in industry through transparency and willingness to engage in discussions with the public might also mitigate public concerns.